Innovative Teaching Materials for Balaghah: Enhancing Literary Appreciation through Syawahid Adabiyah in Ilmu Badi' - Ulin Nuha, Muhammad Afthon; Ahmad Fikri Amrullah; Rizka Widayanti; Ida Fauziatun Nisa’; Murdiono Murdiono (Universitas Islam Negeri Jurai Siwo Lampung, 2024)
This study aims to develop innovative teaching materials for Balaghah and Ilmu Badi' using Syawahid Adabiyah to enhance literary appreciation among students in the Arabic Language Education Program at UIN Sayyid Ali Rahmatullah Tulungagung. The term